Acute Disseminated Intravascular Coagulation Due to Oxaliplatin; Azithromycin-Induced Stevens-Johnson Syndrome; Acute Jugular Vein Thrombosis with Rituximab; Hemorrhagic Bullae of the Fingers Induced by Furosemide. Issue 1 (January 2017) - Mancano, Michael A.
The purpose of this feature is to heighten awareness of specific adverse drug reactions (ADRs), discuss methods of prevention, and promote reporting of ADRs to the US Food and Drug Administration's (FDA's) MedWatch program (800-FDA-1088). If you have reported an interesting, preventable ADR to MedWatch, please consider sharing the account with our readers. Your report will be published anonymously unless otherwise requested. This feature is provided by the Institute for Safe Medication Practices (ISMP) in cooperation with the FDA's MedWatch program and Temple University School of Pharmacy. ISMP is an FDA MedWatch partner.